Novel hydrothermal synthesis of MoS2 nanocluster structure for sensitive electrochemical detection of human and environmental hazardous pollutant 4-aminophenol. Issue 46 (22nd April 2016) - Kumar, J. Vinoth; Karthik, R.; Chen, Shen-Ming; Saravanakumar, K.; Govindasamy, Mani; Muthuraj, V.
Abstract : A trace level electrochemical detection platform for the determination of environmentally hazardous pollutant 4-aminophenol at MoS2 nanoclusters is reported. Abstract : Herein, we have demonstrated a new electrochemical sensor for trace level detection of environmentally hazardous 4-aminophenol (4-AP) using a glassy carbon electrode (GCE) modified with MoS2 nanoclusters. The MoS2 nanoclusters were fabricated by a simple hydrothermal treatment without using any other organic templates or surfactants. The formation of MoS2 nanoclusters was confirmed by X-ray diffraction, FT-infrared, Raman and energy dispersive X-ray spectroscopies, scanning electron and transmission electron microscopies and selected area electron diffraction studies. The MoS2 modified GCE (MoS2 /GCE) shows good electrocatalytic activity towards the redox reaction of 4-AP by means of cyclic voltammetry and differential pulse voltammetry. The DPV detection of 4-AP using MoS2 /GCE delivers excellent sensitivity with a low detection limit of 0.03 (±0.008) μM and good linearity in the range of 0.04–17 μM. The sensitivity of the developed electrode is 4.278 (±0.058) μA mM −1 cm −2 . The developed sensor displayed good repeatability, reproducibility and selectivity. Moreover, the practical applicability of the MoS2 /GCE is demonstrated in water samples which delivered satisfactory recoveries.